Penggunaan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar - Ansya, Yusron Abda'u; Salsabilla, Tania (ARZUSIN, 2024)
The aim of this research is to describe how the application of the Problem Based Learning model can be an effective solution in overcoming the problem of low student learning outcomes in science and science subjects in class V elementary schools. This research uses a qualitative approach with descriptive methods. This research was carried out in Class V of SD Muhammadiyah T.A. 2024/2025. The results of the research show that the three main problems faced are low understanding of the material as reflected in the UTS results under KKM, lack of motivation and active involvement of students in learning which can be seen from their lack of enthusiasm, disorganization and lack of focus during lessons, and low student discipline which disrupts the creation of an atmosphere. conducive learning. Thus, the application of the Problem Based Learning model in science and science learning in elementary schools can be an effective solution to overcome low student learning outcomes and increase the learning motivation of fifth grade elementary school students.